2019
DOI: 10.1021/acs.joc.9b00442
|View full text |Cite
|
Sign up to set email alerts
|

From Tetrahydrofurans to Tetrahydrobenzo[d]oxepines via a Regioselective Control of Alkyne Insertion in Rhodium-Catalyzed Arylative Cyclization

Abstract: The formation of chiral 5- and 7-membered tetrahydrofurans and tetrahydrobenzo­[d]­oxepines is achieved via arylative cyclization of simple O-tethered alkyne-enoates in the presence of arylboronic acids and chiral dienes-rhodium catalyst under mild conditions. Access to such structures was achieved via a simple switch in the regioselectivity of the alkyne insertion thanks to a proper choice of the alkyne substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…13 C kinetic isotopic effect (KIE) experiments of a substrate at natural abundance revealed a significant 13 C KIE for Chemistry-A European Journal the nitrile carbon, suggesting that the addition to the nitrile (58 to 59) is likely the rate-determining step (RDS); however, the transmetalation step cannot be ruled out as the RDS. Finally, 31 P NMR studies suggested that water aids the transmetalation step.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 3 more Smart Citations
“…13 C kinetic isotopic effect (KIE) experiments of a substrate at natural abundance revealed a significant 13 C KIE for Chemistry-A European Journal the nitrile carbon, suggesting that the addition to the nitrile (58 to 59) is likely the rate-determining step (RDS); however, the transmetalation step cannot be ruled out as the RDS. Finally, 31 P NMR studies suggested that water aids the transmetalation step.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Rhodium-, [19][20][21][22][23][24][25][26][27][28][29][30][31] palladium-, [32][33][34][35][36][37][38][39][40][41] or copper-catalyzed [42] arylative cyclizations of alkyne-tethered electrophiles involving 1,2arylmetallation of the alkyne to place the metal proximal to the electrophile, followed by direct intramolecular trapping of the intermediate alkenylmetal species with the tethered electrophile (see Scheme 1A), have been reported extensively. However, the use of catalyst systems based upon other metals are of interest because this could allow access to new reactivity and different reaction outcomes, with a consequent increase in scope.…”
Section: Syn-arylmetallative Cyclizations Of Alkyne-tethered Electrop...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several cyclizations of diverse substrates have been developed covering both indolylboronic acids and transition-metal catalysis. In 2019, the Darses research group developed a methodology for the asymmetric cyclization of (allyl)propargylether catalyzed by a rhodium catalyst (Scheme 43) [173]. The reaction is performed in methanol at 60 °C, and the reaction outcome depends on the structure of the ligand.…”
Section: Chemical Transformations Of Indolylboronic Acid Derivativesmentioning
confidence: 99%